The Difference In The Effect of Ankle Strategy Exercise And Tandem Strategy Exercise On The Risk of Falls In Elderly Withhypertension At Nalumsari Community Health Center 1 - Ade Fazal Muna; Sukesih; Dewi Hartinah (International Journal of Health and Pharmaceutical (IJHP), 2026)
Hypertension in the elderly can cause balance disorders that increase the risk of falls, so effective balance training interventions are needed. This study aims to analyze the differences in the effects of Ankle Strategy Exercise and Tandem Strategy Exercise on the risk of falls in hypertensive elderly at Nalumsari 1 Community Health Center. The study used a quantitative approach with a quasi-experimental design with a pre-test and post-test design in two groups. The study population was 66 hypertensive elderly, while a sample of 40 respondents was selected using a simple random sampling technique. The research instruments included the Timed Up and Go Test, a sphygmomanometer, a stopwatch, and an observation sheet. Data analysis was carried out using univariate analysis, the Shapiro-Wilk normality test, the Wilcoxon Signed Rank Test, and the Mann-Whitney test. The results showed that both groups experienced a significant decrease in Timed Up and Go Test scores after the intervention with a p value = 0.000. The results of the Mann-Whitney test showed a significant difference in effectiveness between the two groups with a p value = 0.003, where the Tandem Strategy Exercise group had a higher mean rank than the Ankle Strategy Exercise group. It can be concluded that both exercises are effective in reducing the risk of falls in elderly hypertensive patients, but Tandem Strategy Exercise provides better effectiveness than Ankle Strategy Exercise.